SPIRITUALITAS DAN SUKACITA PEWARTA INJIL DI KEVIKEPAN TORAJA BERLANDASKAN EVANGELII GAUDIUM - Natalia Putri Liling; Frans Fandy Palinoan (LP2M STIKPAR Toraja, 2024)
Proclaiming the Gospel today is not an easy thing, for many challenges arise when conducting the work of proclamation. Cultural differences in various places and fields are some of the challenges in proclamation, and the same also happens in the Vicariate of Toraja. Technological developments have brought changes to human life, including to the Catholics in the Vicariate of Toraja. The use of technology has become a part of human life. However, it is undeniable that there are still people who cannot use gadgets. Therefore, evangelists in society are very necessary. This research aims to see how the spirituality of the evangelists in the Vicariate of Toraja is like and whether there is joy felt by the evangelists in the Vicariate of Toraja. The method used in this research is qualitative method. The Evangelii Gaudium document is the main source for this research. The author concludes that the success of a Gospel proclamation depends on the personality of the evangelist. The evangelists in the Vicariate Toraja have high missionary spirit. Even though they face many challenges in their work of proclaiming the Gospel, this does not dampen the enthusiasm of the evangelists. Apart from that, the use of technology also helps evangelists, either personally or for the purposes of proclaiming the Gospel. Before carrying out a proclamation, it is good for an evangelist to have preparations so that the proclamation can be conducted well and have impact on the people.